Clinical Pharmacy Services and Human Resources Requirements at MOH Primary Healthcare Centers during Ten years Mass Gathering Hajj (2006-2015) in Makah and Al-Medina Regions, Saudi Arabia - Alomi, Yousef Ahmed; Alhennawi, Khairat; Khayayt, Nizar (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the clinical pharmacy services and workforce requirements at Ministry of Health primary health care centers during mass gathering Hajj ten years (2006-2015) at Makah and Al-Medina Regions in Saudi Arabia. Methods: It is a retrospective analysis of ten years (2006-2015) of MOH primary health care centers (PCC) pharmacies during mass gathering Hajj period (15-30 days). The clinical pharmacist should provide pharmaceutical care to all patients either Pilgrim or not Pilgrim at Makah region. It included Mona holy places hospitals; Arafat holy places hospitals, and Makah city. The workforce requirements calculated based on MOH workforce standards of hospitals. The clinical activities drive from MOH critical care services, and emergency services, and mortality rate data. The nine clinical pharmacy services characterized by reduction mortality cost saving and mass gathering demand chosen. American College of Clinical Pharmacy (ACCP) model of clinical activities used. Results: The total number of Pilgrims was (1,952,817-3,161,573) with average (2,445,208). The average number of clinical pharmacists needed was (41.7 FTE) at holy places Primary Care Centers, while (94 FTE) at primary care centers in Makah city, and (16.6 FTE) at primary care centers at Al-Medina Region. The total number of clinical pharmacists needed per 10,000 population was (244.52 FTE) in Makkah region while (195.28 FTE) in Al-Madina region. Conclusion: There is a much demand of clinical pharmacist at primary care centers during mass gathering Hajj period in Makkah and Al-Madina regions. The clinical pharmacist in plays very vital role in public society especially chronic illness with emphasis mass gathering of reducing morbidity and mortality. In addition to preventing unnecessary additional cost.
Keywords: Clinical Pharmacy; Primary Care Center; Workload; Workforces; Mass Gathering; Hajj